Efektivitas Metode Tikrar dalam Pembelajaran Tahfidz di SD Darul Hikam Bandung - Kinesti, Rakanita Dyah Ayu; Lusiana, Anita; Oktaviana, Elisa; Azizah, Ria Nur; Falsafiya, Faza Naf’a; Zahro, Tsaniya Fatimatuz (TSAQOFAH, 2022)
This study aims to determine how the implementation of the tahfidz program with the tikrar method and the effectiveness of the use of the tikrar method in learning tahfidz at the Darul Hikam Elementary School (SD) Bandung. This study uses a qualitative descriptive method of field study. Data collection techniques through observation, interviews, and documentation. Data analysis uses data collection techniques, data reduction, data presentation, then drawing conclusions. The subjects of this study were several SD Darul Hikam teachers and the object of this research was the effectiveness of the tikrar method. The results showed that the use of the tikrar method in learning tahfidz at SD Darul Hikam was considered very effective. The tikrar method is applied by repeating the verses to be memorized by looking at the manuscripts, then memorizing them without looking at the manuscripts. These steps are then applied to memorize the verses that follow and are combined with the verses that have been memorized before. In these ways, students will not feel burdened in memorizing. The effectiveness of the tikrar method is shown by the ability of students to memorize up to 7 juz within a year.